An Atomistic Tomographic Study of Oxygen and Hydrogen Atoms and their Molecules in CVD Grown Graphene. Issue 44 (9th October 2015) - Baik, Sung‐Il; Ma, Lulu; Kim, Yoon‐Jun; Li, Bo; Liu, Mingjie; Isheim, Dieter; Yakobson, Boris I.; Ajayan, Pulickel M.; Seidman, David N.
Abstract : The properties and growth processes of graphene are greatly influenced by the elemental distributions of impurity atoms and their functional groups within or on the hexagonal carbon lattice. Oxygen and hydrogen atoms and their functional molecules (OH, CO, and CO2 ) positions' and chemical identities are tomographically mapped in three dimensions in a graphene monolayer film grown on a copper substrate, at the atomic part‐per‐million (atomic ppm) detection level, employing laser assisted atom‐probe tomography. The atomistic plan and cross‐sectional views of graphene indicate that oxygen, hydrogen, and their co‐functionalities, OH, CO, and CO2, which are locally clustered under or within the graphene lattice. The experimental 3D atomistic portrait of the chemistry is combined with computational density‐functional theory (DFT) calculations to enhance the understanding of the surface state of graphene, the positions of the chemical functional groups, their interactions with the underlying Cu substrate, and their influences on the growth of graphene. Abstract : 3D atomistic portrait of the chemistry of graphene on an atomic scale, oxygen and hydrogen atoms, and their functional molecules, OH, CO, and CO2, whose positions and chemical identities are mapped in a graphene monolayer film grown on a copper substrate, at the atomic part‐per‐million (atomic ppm) detection levels employing 3D atom‐probe tomography.